1988
DOI: 10.1017/s0021859600081314
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments comparing ammonium nitrate and urea top-dressing for winter cereals and grassland in the U.K.

Abstract: The results of 173 field experiments carried out between 1957 and 1986 are presented comparing ammonium nitrate and urea as top-dressings for winter cereals and grassland.The trials show that urea was an inferior nitrogen source to ammonium nitrate. The yield from ammonium nitrate was significantly greater than that from urea for winter wheat, winter barley and for first, second and third cut silage. The results suggest (a) that winter wheat and winter barley respond differently to the two nitrogen sources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
5
16
1
Order By: Relevance
“…This was reflected in the calculated N use efficiency which was 55% higher with CAN compared with urea, the value of URY (c.90%) and relative N uptake (c.85%). The relatively lower agronomic performances encountered with urea agrees closely with the conclusions reached by Chaney and Paulson (1988) for (early) spring applications of N. Although the uptake of un-hydrolysed urea had been reported (Mengel and Kirkby, 1987), its rate of absorption is relatively lower compared with ammonium-N or nitrate-N (Bradley et al, 1989). Watson et al (1990) suggested that the translation of N uptake into DMY may be less effective with urea than CAN.…”
Section: Comparison Of the Three N Sourcessupporting
confidence: 83%
See 4 more Smart Citations
“…This was reflected in the calculated N use efficiency which was 55% higher with CAN compared with urea, the value of URY (c.90%) and relative N uptake (c.85%). The relatively lower agronomic performances encountered with urea agrees closely with the conclusions reached by Chaney and Paulson (1988) for (early) spring applications of N. Although the uptake of un-hydrolysed urea had been reported (Mengel and Kirkby, 1987), its rate of absorption is relatively lower compared with ammonium-N or nitrate-N (Bradley et al, 1989). Watson et al (1990) suggested that the translation of N uptake into DMY may be less effective with urea than CAN.…”
Section: Comparison Of the Three N Sourcessupporting
confidence: 83%
“…Ammonia volatilisation increases significantly with the application rate of urea (Overrein and Moe, 1967) which is one of the main reasons for urea to result in lower yields relative to CAN or AN (Lloyd, 1992;Chambers and Dampney, 2009). This effect had been shown in earlier studies (Chaney and Paulson, 1988;Murphy, 1983;Van Burg et al, 1982) and it can be the reason for the relatively lower response to urea-N in the range of 50 to 75 kg ha -1 . The differences in the response between fertilisers are expected to be greater at higher N application rates than those used in this study (Overrein and Moe, 1967).…”
Section: Comparison Of the Three N Sourcessupporting
confidence: 59%
See 3 more Smart Citations